2022
DOI: 10.1038/s41467-021-27941-x
|View full text |Cite
|
Sign up to set email alerts
|

Can electric fields drive chemistry for an aqueous microdroplet?

Abstract: Reaction rates of common organic reactions have been reported to increase by one to six orders of magnitude in aqueous microdroplets compared to bulk solution, but the reasons for the rate acceleration are poorly understood. Using a coarse-grained electron model that describes structural organization and electron densities for water droplets without the expense of ab initio methods, we investigate the electric field distributions at the air-water interface to understand the origin of surface reactivity. We fin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
168
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(181 citation statements)
references
References 67 publications
12
168
1
Order By: Relevance
“…14−18 This may be attributed to the strong electric field across the GLI. 19,20 In this study case, we even observed that the TEMPO was reduced by losing its oxyl group (m/z 142) or hydrogenated to form the ions at m/z 157 and 158 (Figure 3a). These results also proved the special redox environment of the GLI and its critical role in the CO 2 reduction.…”
mentioning
confidence: 60%
“…14−18 This may be attributed to the strong electric field across the GLI. 19,20 In this study case, we even observed that the TEMPO was reduced by losing its oxyl group (m/z 142) or hydrogenated to form the ions at m/z 157 and 158 (Figure 3a). These results also proved the special redox environment of the GLI and its critical role in the CO 2 reduction.…”
mentioning
confidence: 60%
“…If we assume that this potential acts over 5 × 10 −8 cm, this corresponds to an electric field of 2 × 10 7 to 4 × 10 7 V/cm. Recently, Head-Gordon and coworkers ( 44 ) calculated that the electric field alignments along free O–H bonds at the AWI are ∼1.6 × 10 7 V/cm larger on average than that found for O–H bonds in the interior of the water droplet. This estimate is in good agreement with the measured electric field strength of a water microdroplet in oil ( 45 ).…”
Section: Resultsmentioning
confidence: 90%
“…Other interfacial effects have been considered in explaining observed reaction acceleration ( Fallah-Araghi et al, 2014 ; Yan et al, 2016 ; Lee et al, 2017 , 2019a , 2019b , 2020 ; Zhou et al, 2018 ; Wei et al, 2020 ; Xiong et al, 2020 ; Huang et al, 2021 ), including the extreme pH at the droplet surface ( Basuri et al, 2020 ; Huang et al, 2021 ), preferential orientation of reactants ( Zhou et al, 2018 ; Narendra et al, 2020 ), and strong electric fields (on the order of MV/cm) at or near the microdroplet interface ( Lee et al, 2019b , 2020 ; Xiong et al, 2020 ). The existence of the strong fields is supported by spectroscopic ( Xiong et al, 2020 ) and computational ( Leung, 2010 ; Kathmann et al, 2011 ; Yesibolati et al, 2020 ; Hao et al, 2022 ) data for aqueous microdroplets. The electric field lowers the energy barrier for reaction by stabilizing the transition state or by activating the reactant.…”
Section: Introductionmentioning
confidence: 82%